2017
DOI: 10.1177/000313481708301228
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Transport and Clinical Outcome in Rural Trauma: A Helicopter versus Ambulance Comparison

Abstract: Helicopter Emergency Medical Services (HEMS) is presumably an effective way of patient transport in rural trauma, yet the literature addressing its effectiveness is scarce. In this study, we compared the clinical outcome of rural trauma patients between Ground Emergency Medical Services (GEMS) and HEMS transportation from the beginning of 2006 to the end of 2012. Focus was placed on identifying factors associated with survival to discharge in these patients. Over the seven-year study period, 4492 patients met … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Similarly to other systems, trauma formed the largest subset of patients. Trauma is indeed the most common cause of preventable death in the previously healthy [33]., and several studies have found HEMS to provide benefit to this specific patient group [34][35][36]. The second most common medical problem was OHCA, representing a large proportion compared to other systems [7,8,21].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to other systems, trauma formed the largest subset of patients. Trauma is indeed the most common cause of preventable death in the previously healthy [33]., and several studies have found HEMS to provide benefit to this specific patient group [34][35][36]. The second most common medical problem was OHCA, representing a large proportion compared to other systems [7,8,21].…”
Section: Discussionmentioning
confidence: 99%
“…Injury severity scoring measures were used in 73 (76%) articles to risk stratify and cohort similarly injured sub-groups of trauma patients, of which 54 (74%) used anatomic severity measures (injury severity score [ISS], abbreviated injury score [AIS], new injury severity score [NISS]); 3 (3%) used physiologic or hybrid scores (e.g., trauma injury severity score [TRISS]); and 17 (18%) used a combination of anatomic, physiologic, and/or hybrid scores (e.g., revised trauma score [RTS]). There were only a few studies that measured organ failure as a secondary outcome—four (4%) articles used multiple organ failure as a secondary outcome [ 27 , 63 , 64 , 85 ] assessed by the Sequential Organ Failure Assessment (SOFA) score, and two (2%) studies specified acute renal failure as the organ failure outcome [ 69 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…). There were only a few studies that measured organ failure as a secondary outcome-four (4%) articles used multiple organ failure as a secondary outcome [27,63,64,85] assessed by the Sequential Organ Failure Assessment (SOFA) score, and two (2%) studies specified acute renal failure as the organ failure outcome [69,81].…”
Section: Main Outcomesmentioning
confidence: 99%
“…The injury severity and major internal bleeding was misjudged by the primary EP, leading to delayed alert of HEMS. Beside the time benefit of air rescue regarding transportation to level 1 trauma centers in rural areas, HEMS also provides survival benefit for trauma patients [8][9][10]. Studies have shown that survival time is also being improved by usage of a correct emergency tactic.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that survival time is also being improved by usage of a correct emergency tactic. Especially in rural areas patients admitted to hospital via HEMS tend to have a better outcome, even if initially presented with a worse overall condition [8,9,11]. In order to identify cases in which HEMS should be considered different scoring systems have been developed to help the emergency responder.…”
Section: Discussionmentioning
confidence: 99%